The armed conflict and peacebuilding in Colombia - C. U. Ochoa; B. P. Mejía (Law and Safety)
The study analyzes the processes that have contributed to the configuration of Colombia’s internal armed conflict and to the different peace proposals promoted by national governments for the last 40 years. It explores the causes and consequences of the armed conflict and the implications of building a culture of peace for the Colombian people. This is achieved through a review of the theoretical, contextual, and historical primary and secondary sources relevant to these two thematic axes. Finally, proposals to be undertaken under bilateral agreements for the end of the armed conflict and for a fair and lasting peace are outlined.